2020
DOI: 10.1101/2020.06.16.153361
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivofluorescence lifetime imaging captures metabolic changes in macrophages during wound responses in zebrafish

Abstract: 39The effector functions of macrophages across the spectrum of activation states in vitro are linked to 40 profound metabolic rewiring. However, the metabolism of macrophages remains poorly characterized in 41 vivo. To assess changes in the intracellular metabolism of macrophages in their native inflammatory 42 microenvironment, we employed two-photon fluorescence lifetime imaging microscopy (FLIM) of 43 metabolic coenzymes NAD(P)H and FAD. We found that pro-inflammatory activation of macrophages in 44 vivo wa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The use of fluorescent reporter mice in the current study provided macrophage-specific labels while circumventing these issues of antibody delivery and non-specific binding. The mCherry reporter used in the current study also did not interfere with NAD(P)H and FAD autofluorescence, similarly observed in previous in vivo autofluorescence studies (Hoffmann and Ponik, 2020;Miskolci et al, 2020). Identifying macrophage-specific autofluorescence features without fluorescent reporters remains challenging to due to substantial macrophage heterogeneity in vivo.…”
Section: Discussionsupporting
confidence: 75%
“…The use of fluorescent reporter mice in the current study provided macrophage-specific labels while circumventing these issues of antibody delivery and non-specific binding. The mCherry reporter used in the current study also did not interfere with NAD(P)H and FAD autofluorescence, similarly observed in previous in vivo autofluorescence studies (Hoffmann and Ponik, 2020;Miskolci et al, 2020). Identifying macrophage-specific autofluorescence features without fluorescent reporters remains challenging to due to substantial macrophage heterogeneity in vivo.…”
Section: Discussionsupporting
confidence: 75%
“…M1-like macrophages have upregulated glycolysis while M2-like macrophages generally are more dependent on oxidative metabolism [ 34 ]. These metabolic differences between M1-like and M2-like macrophages are detected by autofluorescence imaging of NAD(P)H and FAD [ 41 - 45 ]. High resolution optical imaging, combined with single-cell segmentation, allows quantification of the changes in metabolism at the cell level, and successfully distinguishes subpopulations of macrophages [ 15 ].…”
Section: Autofluorescence Imaging For Quality Control Of Cytotherapiesmentioning
confidence: 99%
“…Although the combination of autofluorescence lifetime imaging with SHG imaging is currently underexplored for the characterization of cell-seeded biomaterials and scaffolds, we expect increased use of autofluorescence lifetime imaging concurrent with SHG imaging for characterization of regenerative engineered devices. NAD(P)H and FAD fluorescence lifetime imaging allows differentiation of macrophage phenotypes, due to their different metabolic activities [ 41 - 45 ]. Since the pro-inflammatory macrophage (M1) and anti-inflammatory macrophage (M2) macrophages exhibit different immune functions, autofluorescence imaging can be used to study macrophage polarization states to monitor wound healing progression.…”
Section: Multimodal Autofluorescence and Shg Imaging For Tissue Regen...mentioning
confidence: 99%